Strain Conditions Monitoring on Corroded Prestressed Steel Strands in Beams Based on Fiber Bragg Grating Sensors - Fan, Guo-Xi (Sensors (Basel), 2020)
Fiber Bragg Grating (FBG) sensors, with excellent properties, have been widely adopted to monitor the mechanical parameters in civil engineering in recent years. On the other hand, the current study on fatigue performance of corroded prestressed steel strands is still limited, and this is mainly because the long-term strain conditions monitoring is difficult to conduct. Based on the aforementioned considerations, a total of six beam specimens were fabricated in this study. The loading mode of four points bending was adopted in the form of sinusoidal waves in the experiments. On basis of the experimental results, it can be concluded that the fatigue life of the beam decreases sharply with the increase of the corrosion rate of steel strands. Besides, with the increase of the maximum fatigue load, the fatigue life of the beam will decrease significantly. Furthermore, the existing fatigue damage of steel strand inside the beam before corrosion may further accelerate its fatigue failure. As a result, the fatigue life of the beam is reduced because of the stress concentration. Under the same external load, the strain increment and the residual strain of steel strands in the stages of loading and unloading after corrosion increase significantly compared with other stages, while the existing residual strain always shows an increasing trend at various static loading stages. Therefore, the corrosion of steel strand seriously affects not only its mechanical properties, but also its fatigue performance. Finally, the FBG sensors are capable of measuring the steel strand strain, as well as the long-term strain conditions.